PWE-164 A Meta-analysis Of Randomised Controlled Trials On The Effect Of Probiotics On Functional Constipation In Adults. (9th June 2014) - Dimidi, E; Christodoulides, S; Fragkos, KC; Scott, SM; Whelan, K
Abstract : Introduction: Constipation is a prevalent gastrointestinal disorder whose treatment remains challenging. Patient dissatisfaction with prescribed medications is common, and there is a need for alternative methods of management. Probiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit to the host, and have been increasingly used in the management of functional constipation. The aim of this study was to determine the effect of probiotics in functional constipation through a systematic review and meta-analysis of randomised controlled trials (RCTs) in adults. Methods: Methods followed PRISMA recommendations. Studies were identified by searching four electronic databases, back-searching reference lists, contacting authors and hand searching abstracts of eight annual conferences. RCTs reporting administration of probiotics in adults with functional constipation were included. Two reviewers independently performed the screening of articles, data extraction, and risk of bias assessment. Data were synthesised using weighted or standard mean differences for all relevant outcomes using a random effects model. Publication bias was assessed via funnel plots and the Egger's test. Results: 657 records were identified, of which 14 were eligible (1, 347 patients). Probiotics significantly reduced whole gut transit time by 11.9 h (95% CI: -18.4 to -5.4; p = 0.0003). They also significantly reduced right and left colonic transit times by 5.7 h (95% CI: -9.9 to -1.6; p = 0.007) and 5.1 h (95% CI: -9.6 to -0.6; p = 0.03), respectively. Probiotics significantly increased stool frequency by 1.1 bowel movements per week (95% CI: 0.7 to 1.5; p < 0.0001) with a number to treat (NNT) of 2, but there was significant heterogeneity (I 2 =79%; p < 0.0001). Probiotics resulted in softer stool consistency (standardised mean difference, SMD = +0.5, 95% CI: 0.3 to 0.8; p = 0.0001) with a NNT of 3. Bloating (SMD = -0.6, 95% CI: -1.2 to -0.01; p= 0.04) and flatulence (SMD = -0.4, 95% CI: -0.7 to -0.1; p = 0.01) were also significantly reduced. No serious adverse events were reported following probiotic administration, and compliance was over 95%. There was no statistically significant funnel plot asymmetry found (p = 0.271), suggesting no evidence of publication bias. Conclusion: Probiotics significantly improve gut transit time, stool frequency and consistency, and constipation-related symptoms, and are associated with low risk of adverse events and high rates of compliance. Probiotics should thus be considered as an alternative treatment for functional constipation. Disclosure of Interest: E. Dimidi Grant/research support from: Nestec Ltd, S. Christodoulides Grant/research support from: Nestec Ltd, K. Fragkos: None Declared, S. M. Scott: None Declared, K. Whelan: None Declared.